Narativne strategije v pridigah Matije Vertovca - Bošnjak, Blanka (Jezik in slovstvo, 2016)
Matija Vertovec (1784-1851) was born in Vipavsko. As a priest, he was also engaged in history, geography, chemistry, physics and astronomy, as well as agriculture, wine-growing and winery in particular. He was a member of Bleiweis's Novice from the day of their establishment in 1843. Vertovec was a popular preacher and published some of his selected sermons and speeches in the book Shodni ogovori (1850), in which we can find various narrative strategies and structures: rhetorically formed narrative examples, the drama of events, picturesque descriptions, imagination, intertextual processes, etc.
Keywords: Vertovec, Matija, 1784-1851; "Shodni ogovori"; Slovene literature; slovenska književnost; pridige; narativne strategije; 19.st.